Labmade metallizer: Deposition of aluminum film on glass substrate and subsequent anodization to obtain aluminum oxide - Mezavila-Garcia, Uanderson; Santos, Janaina S.; Rangel, Elidiane C. [UNESP]; Cruz, Nilson C. [UNESP]; Trivinho-Strixino, Francisco (Sociedade Brasileira de Quimica (SBQ), 2021)
In this work, the assembly of a low-cost metallizer is presented, based on physical vapor deposition, to obtain metallic aluminum film d eposited o ver a g lass s ubstrate. L ater, t he A l fi lm is an odized an d converted into a porous nanostructured oxide film. T he metallic fi lm thickness wa s measured by profilometry, and t he sample p osition inside t he chamber w as evaluated. Samples positioned at the center of the sample holder showed considerable thickness and best homogeneity compared to those samples positioned at the edges of the sample holder. A thick metallic film of A l (6 to 7 µm) was deposited over the glass substrate for subsequent anodizing treatment. Mild anodization allowed the total conversion of metallic Al after 7000 s, producing a transparent anodic aluminum oxide (AAO) film adhered to the glass substrate. The AAO morphology was investigated by SEM. Some factors have been listed to describe the low regularity and homogeneity of nanopores in the outer layer of AAO, such as internal defects, compaction of deposited Al film layers and the glass substrate roughness.
Metalizadora construída em laboratório: Deposição de filme de alumínio sobre substrato de vidro e posterior anodização para obtenção de óxido de alumínio
Keywords: Anodic aluminum oxide; Low-cost metallizer; Metallization of Al